Preclinical evaluation of tolvaptan and salsalate combination therapy in a Pkd1-mouse model - Song, Xuewen; Leonhard, Wouter N.; Kanhai, Anish A.; Steinberg, Gregory R.; Pei, York; Peters, Dorien J. M. (Frontiers in Molecular Biosciences, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic disorder and an important cause of end stage renal disease (ESRD). Tolvaptan (a V2R antagonist) is the first disease modifier drug for treatment of ADPKD, but also causes severe polyuria. AMPK activators have been shown to attenuate cystic kidney disease. In this study, we tested the efficacy of the combined administration of salsalate (a direct AMPK activator) and tolvaptan using clinically relevant doses in an adult-onset conditional Pkd1 knock-out (KO) mouse model. Compared to untreated Pkd1 mutant mice, the therapeutic effects of salsalate were similar to that of tolvaptan. The combined treatment tended to be more effective than individual drugs used alone, and was associated with improved kidney survival (P < 0.0001) and reduced kidney weight to body weight ratio (P < 0.0001), cystic index (P < 0.001) and blood urea levels (P < 0.001) compared to untreated animals, although the difference between combination and single treatments was not statistically significant. Gene expression profiling and protein expression and phosphorylation analyses support the mild beneficial effects of co-treatment, and showed that tolvaptan and salsalate cooperatively attenuated kidney injury, cell proliferation, cell cycle progression, inflammation and fibrosis, and improving mitochondrial health, and cellular antioxidant response. These data suggest that salsalate-tolvaptan combination, if confirmed in clinical testing, might represent a promising therapeutic strategy in the treatment of ADPKD.